Analysis of Increasing Trends in Hemodialysis Patients and Its Implications for National Health Financing Burden in Indonesia: Literature Study - Fahny, Vira Zul; Rahma, Putri Aulia; Gurning, Fitriani Pramita (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
The number of chronic kidney disease (CKD) patients undergoing hemodialysis in Indonesia continues to increase, putting great pressure on the national health financing system, especially the National Health Insurance (JKN). This study is a literature review that analyzes five scientific articles published between 2021 and 2024. Articles were selected through targeted searches in Google Scholar and PubMed, then synthesized narratively to describe trends and financing implications. The synthesis results show a significant increase in the number of hemodialysis patients each year, with therapy costs reaching trillions of rupiah. Payment rates set in the INA-CBGs system are often not in accordance with real costs in hospitals, risking a deficit in health facilities and BPJS Kesehatan. The increasing trend of hemodialysis patients places a large economic burden on the national health system. Cost control strategies are needed through primary prevention, early detection of CKD, adjustment of INA-CBGs rates, and development of alternative therapies to maintain service sustainability.